Composite electrocatalyst of molybdenum disulfide loaded platinum nanoparticles as well as preparation method and application of composite electrocatalyst
By depositing a composite electrocatalyst of platinum nanoparticles on the vertical arrangement structure of the molybdenum disulfide surface, the problems of low hydrogen evolution reaction efficiency and poor catalyst stability in the anion exchange membrane electrolyte cell are solved, and efficient and stable alkaline hydrogen evolution reaction is achieved , meets the demand for industrial hydrogen production.
Patent Information
- Application Number
- CN202411879439.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-19
AI Technical Summary
In anion exchange membrane electrolytic cell, the hydrogen evolution reaction efficiency is low, the overpotential is high, and the catalyst stability is poor, which cannot meet the needs of industrial hydrogen production.
Molybdenum disulfide-supported composite electrocatalysts, which deposit platinum nanoparticles on the vertically arranged structure of the MoS2 surface, and use edge sulfur atoms to work synergistically with Pt nanoparticles to reduce the hydrolysis reaction energy barrier and promote the timely hydrogen Take it out.
It significantly improves the reaction rate of alkaline hydrogen evolution reaction, reduces the overpotential, improves the stability of the catalyst, can operate stably for a long time under high current density, and has better performance than commercial Pt/C.
Smart Images

Figure CN119465277A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of green hydrogen production by electrolysis of water, and in particular to a method for preparing a composite electrocatalyst. Background Art
[0002] With the continuous development of human society, energy demand continues to increase. The use of traditional fossil energy will emit a large amount of carbon dioxide and other pollutants, causing serious pollution to the environment. Hydrogen has the advantages of no pollution and high energy density. It is one of the most effective energy carriers to replace traditional fossil fuels. It has been widely used in hydrogen fuel cell vehicles, deuterium nuclear accelerators, production and processing of non-ferrous metals, petroleum refining, etc.
[0003] Using solar energy, wind energy and other energy to generate electricity, and producing green hydrogen through water electrolysis, can produce high-purity hydrogen (>95%), and this process does not emit any carbon dioxide, which is a hydrogen production technology with great development potential. Among the many water electrolysis hydrogen production technologies, anion exchange membrane electrolyzers have the advantages of high efficiency, economy, and reliability, which are conducive to large-scale hydrogen production and have great development value. However, in the hydrogen production process of anion exchange membrane electrolyzers, the hydrogen evolution reaction produces water dissociation, hydrogen desorption and hydrogen generation processes under alkaline conditions, involving multiple reaction steps and proton migration processes, resulting in low efficiency of hydrogen evolution reaction in the electrolyzer under low potential conditions and high over-points; at the same time, at ampere-level current density, the catalyst stability is poor and cannot meet the actual needs of industrial hydrogen production.
[0004] The design of existing hydrogen evolution reaction (HER) catalysts adopts a multi-metal active site strategy to significantly improve the activity of HER in alkaline media through the synergistic effect of multi-site metal active sites. For example, by modifying ruthenium (Ru) on the platinum (Pt) surface, the water dissociation ability can be enhanced, thereby reducing the reaction energy and improving the HER efficiency. In addition, non-precious metals (such as nickel (Ni), molybdenum (Mo), cobalt (Co), etc.) can also be used to construct multi-site active sites to promote the dissociation of water and the generation of hydrogen. For example, Ni-Pt active sites are formed by amorphous Ni(OH)2-coated platinum nanoparticles, showing good HER activity; Mo-Co active sites are formed by single molybdenum atom-doped CoOx; Ni-Mo active sites are constructed by NixMoy alloy / hydroxide interface; Ni-Cr-Cu active sites are formed by Cu foam co-modified with Ni and CrOx. These active sites effectively promote the dissociation of water through the synergistic effect between metals and non-metals. However, due to the strong adsorption between metal atoms and hydrogen groups, the HH coupling process after water dissociation is hindered, resulting in the inability to form H2 or H2 cannot be desorbed from the catalyst surface, which further leads to low efficiency of hydrogen evolution reaction. In addition, in order to improve the activity of the catalyst hydrogen evolution reaction and reduce the overpotential, researchers have also explored. For example, the patent with publication number CN117822023A discloses a method for preparing a composite electrocatalyst of molybdenum disulfide loaded with platinum nanoclusters for alkaline water electrolysis hydrogen production, by constructing MoS2 with a larger specific surface area and loading more Pt atomic clusters to improve the catalytic activity of water electrolysis. However, this strategy still has some problems, and its electrocatalytic activity has not met expectations; and it depends on controlling the size of platinum and reasonable preparation conditions, which increases the difficulty coefficient of sample preparation. Therefore, how to use less Pt, use simpler experimental steps and further improve the activity of electrocatalysts in hydrogen evolution reaction has become an important issue. Summary of the invention
[0005] In view of the above technical problems, the present invention proposes a composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles and a preparation method and application thereof.
[0006] To achieve the above object, the technical solution of the present invention is implemented as follows:
[0007] A method for preparing a composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles, comprising the following steps:
[0008] (1) Ammonium molybdate ((NH4)6Mo7O 24 ), thiourea (NH2CSNH2) and polyvinylpyrrolidone (PVP) are dissolved in deionized water to obtain a mixed solution I;
[0009] (2) heat-treating the mixed solution I obtained in step (1), centrifuging, washing, and drying to obtain black solid MoS2;
[0010] (3) dispersing the black solid MoS2 obtained in step (2) in a mixed solvent of water and ethanol to obtain a mixed solution II; slowly injecting a Na2[PtCl6]·6H2O aqueous solution into the mixed solution II, subjecting the mixed solution to high temperature treatment so that the Pt atoms are completely deposited on the surface of the MoS2, cooling, filtering, and drying to obtain a product;
[0011] (4) The product obtained in step (3) is annealed to obtain a composite electrocatalyst (Pt / E-MoS2) of molybdenum disulfide loaded with platinum nanoparticles.
[0012] In the above step (1), the mass ratio of ammonium molybdate, thiourea and polyvinyl pyrrolidone is (60-65):(50-55):(28-32); the concentration of ammonium molybdate in the mixed solution I is 30-44 g / L.
[0013] The heat treatment temperature in the above step (2) is 180-260°C and the time is 15-20h.
[0014] Furthermore, in the above step (2), the drying temperature is 30-70° C. and the drying time is 10-15 h.
[0015] In the above step (3), the volume ratio of water to ethanol in the mixed solvent is (7-13):1; the concentration of MoS2 in the mixed solution II is 0.8-1.2 g / L.
[0016] In the above step (3), the concentration of the Na2[PtCl6]·6H2O aqueous solution is 0.7-1.4mmol / L; the rate of slowly injecting the Na2[PtCl6]·6H2O aqueous solution is 10-40min / mL; the volume ratio of the Na2[PtCl6]·6H2O aqueous solution to the mixed solution II is 1:(10-23).
[0017] Furthermore, in the above step (3), the temperature of the high temperature treatment is 90-130° C., and the time is 5-10 h; and the drying is carried out under vacuum conditions, and the drying temperature is 30-70° C., and the time is 10-15 h.
[0018] The annealing temperature in the above step (4) is 260-350°C and the time is 1-5h.
[0019] The composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles prepared by the above-mentioned preparation method, wherein the molybdenum disulfide has a vertically arranged structure and rich edge sulfur sites. This vertically arranged structure not only ensures the availability of edge sites, improves the overall catalytic activity, but also reduces the exposure of the overall surface area, avoids the waste of active sites and unnecessary side reactions. A large number of edge sulfur atoms, on the one hand, can synergize with Pt nanoparticles to effectively reduce the reaction energy barrier of water dissociation; on the other hand, the moderate interaction between sulfur atoms and hydrogen intermediates can ensure the timely release of hydrogen, promote the HH coupling process, and increase the reaction rate of the alkaline hydrogen evolution reaction (HER).
[0020] Application of the above-mentioned composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles in hydrogen evolution reaction under alkaline conditions.
[0021] Furthermore, in the above hydrogen evolution reaction, the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles has a -2 At a current density of 20 mA cm, the overpotential is 35 mV; and at 20 mA cm -2 At a current density of 1.5 MW, the device can run stably for more than 110 hours.
[0022] The beneficial effects produced by the present invention are:
[0023] (1) Enhanced water dissociation ability: The present invention proposes a composite electrocatalyst for producing green hydrogen (HER) under alkaline conditions, specifically a molybdenum disulfide (MoS2) nanostructure rich in sulfur (S) edge sites modified by platinum (Pt) nanoparticles. Among them, molybdenum disulfide is a vertically arranged structure with a nanosphere structure rich in edge features. This is because the spatial restriction of the S atoms at the edge of MoS2 causes Pt atoms to preferentially deposit at the edge of MoS2. The large number of edge sulfur atoms contained in the nanospheres synergize with the Pt nanoparticles to effectively reduce the reaction energy barrier for water dissociation.
[0024] (2) Promote HH coupling: At the same time, the interaction force between sulfur atoms and hydrogen intermediates is moderate, which can ensure the timely release of hydrogen, promote the HH coupling process, and reduce the overpotential. -2 The overpotential is only 35 mV, which improves the reaction rate of alkaline HER.
[0025] (3) Excellent stability: Pt / E-MoS2 prepared by the present invention has a high stability at 20 mA cm -2 It can operate stably for more than 110 hours at a current density of 1.547 W, and its performance is better than that of commercial Pt / C.
[0026] (4) Lower cost: Only a small amount of Pt is used in the composite electrocatalyst prepared by the present invention. For example, in the performance test, the mass fraction of Pt in the prepared sample was only 0.57% when the platinum atomic content was measured by inductively coupled plasma (ICP). In comparison, it is shown that a smaller amount of platinum can achieve a better catalytic effect, saving production costs, which is beneficial to the later industrial production and meeting the actual needs of industrial hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 Spherical aberration corrected scanning transmission electron microscope image of Pt / E-MoS2 at low magnification.
[0029] Figure 2 This is a high-magnification spherical aberration-corrected scanning transmission electron microscope image of Pt / E-MoS2.
[0030] Figure 3 This is the X-ray diffraction spectrum of Pt / E-MoS2.
[0031] Figure 4 This is the X-ray photoelectron spectrum of Pt / E-MoS2.
[0032] Figure 5 High-resolution X-ray photoelectron spectrum of Pt 4f in Pt / E-MoS2.
[0033] Figure 6 This is the linear sweep voltammetry curve of Pt / E-MoS2 as catalyst.
[0034] Figure 7 This is a test diagram of the hydrogen production cycle stability using Pt / E-MoS2 as a catalyst. DETAILED DESCRIPTION
[0035] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] A method for preparing a composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles, comprising the following steps:
[0037] (1) Ammonium molybdate ((NH4)6Mo7O 24 ), thiourea (NH2CSNH2) and polyvinylpyrrolidone (PVP) are dissolved in deionized water to obtain a mixed solution I;
[0038] (2) heat-treating the mixed solution I obtained in step (1), centrifuging, washing, and drying to obtain black solid MoS2;
[0039] (3) dispersing the black solid MoS2 obtained in step (2) in a mixed solvent of water and ethanol to obtain a mixed solution II; slowly injecting a Na2[PtCl6]·6H2O aqueous solution into the mixed solution II, subjecting the mixed solution to high temperature treatment so that the Pt atoms are completely deposited on the surface of the MoS2, cooling, filtering, and drying to obtain a product;
[0040] (4) The product obtained in step (3) is annealed to obtain a composite electrocatalyst (Pt / E-MoS2) of molybdenum disulfide loaded with platinum nanoparticles.
[0041] In the above step (1), the mass ratio of ammonium molybdate, thiourea and polyvinyl pyrrolidone is (60-65):(50-55):(28-32); the concentration of ammonium molybdate in the mixed solution I is 30-44 g / L.
[0042] The heat treatment temperature in the above step (2) is 180-260°C and the time is 15-20h.
[0043] Furthermore, the drying temperature is 30-70°C and the drying time is 10-15h.
[0044] In the above step (3), the volume ratio of water to ethanol in the mixed solvent is (7-13):1; the concentration of MoS2 in the mixed solution II is 0.8-1.2 g / L.
[0045] In the above step (3), the concentration of the Na2[PtCl6]·6H2O aqueous solution is 0.7-1.4mmol / L; the rate of slowly injecting the Na2[PtCl6]·6H2O aqueous solution is 10-40min / mL; the volume ratio of the Na2[PtCl6]·6H2O aqueous solution to the mixed solution II is 1:(10-23).
[0046] Furthermore, in the above step (3), the temperature of the high temperature treatment is 90-130° C., and the time is 5-10 h; and the drying is carried out under vacuum conditions, and the drying temperature is 30-70° C., and the time is 10-15 h.
[0047] The annealing temperature in the above step (4) is 260-350°C and the time is 1-5h.
[0048] Example 1
[0049] The preparation method of the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles in this embodiment comprises the following steps:
[0050] (1) 625 mg of ammonium molybdate ((NH4)6Mo7O 24 ), 525 mg of thiourea (NH2CSNH2) and 300 mg of surfactant PVP were dissolved in 17 mL of deionized water to obtain a uniform mixed solution under stirring.
[0051] (2) The mixed solution prepared in step (1) was placed in a reaction vessel and heated at 220° C. for 17 h.
[0052] (3) The precipitate produced in step (2) is centrifuged, washed, and dried at 50° C. for 13 h to obtain a black solid (MoS2).
[0053] (4) Disperse 140 mg of the black solid obtained in step (3) in 115 mL of a water-ethanol (water to ethanol volume ratio of 10:1) mixed solvent.
[0054] (5) 10 mL of 1.0 mmol / L Na2[PtCl6]·6H2O was injected into the mixed solution obtained in step (4) at a rate of 25 min / mL, and the mixture was incubated at 90°C for 5 h to allow the Pt atoms to be completely deposited on the surface of MoS2. The mixture was filtered and dried at 50°C under vacuum for 13 h.
[0055] (6) The product obtained in (5) was annealed at 300°C for 3h to finally obtain a composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles (Pt / E-MoS2).
[0056] Low-magnification spherical aberration-corrected scanning transmission electron microscope image of the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles prepared in this example ( Figure 1 ) and high-magnification spherical aberration-corrected scanning transmission electron microscopy images ( Figure 2 ) shows that the Pt nanoparticles with a lattice spacing of 0.19 nm are located at the edge of the multilayer MoS2.
[0057] The X-ray diffraction pattern of the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles prepared in this example is as follows: Figure 3 The characteristic diffraction peaks of the sample are located at 14.4°, 33.5°, 39.5° and 58.3° at 2θ, pointing to the (002), (101), (103) and (110) crystal planes of MoS2, respectively.
[0058] The X-ray photoelectron spectrum of the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles prepared in this example is as follows: Figure 4, it can be seen that molybdenum, sulfur, carbon, platinum and oxygen elements exist in the composite material.
[0059] The high-resolution X-ray photoelectron spectrum of the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles prepared in this example is as follows: Figure 5 As can be seen from the figure, platinum exists in the form of metal in the sample. In addition, the mass fraction of Pt is only 0.57% when the content of platinum atoms is measured by inductively coupled plasma (ICP).
[0060] Example 2
[0061] The preparation method of the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles in this embodiment comprises the following steps:
[0062] (1) 600 mg of ammonium molybdate ((NH4)6Mo7O 24 ), 500 mg of thiourea (NH2CSNH2) and 280 mg of surfactant PVP were dissolved in 15 mL of deionized water to obtain a uniform mixed solution under stirring.
[0063] (2) The mixed solution prepared in step (1) was placed in a reaction vessel and heated at 180° C. for 15 h.
[0064] (3) The precipitate produced in step (2) is centrifuged, washed, and dried at 30° C. for 10 h to obtain a black solid (MoS2).
[0065] (4) Disperse 160 mg of the black solid obtained in step (3) in 130 mL of a water-ethanol (water to ethanol volume ratio of 7:1) mixed solvent.
[0066] (5) 13 mL of Na2[PtCl6]·6H2O with a concentration of 0.7 mmol / L was injected into the mixed solution obtained in step (4) at a rate of 10 min / mL, and the mixture was incubated at 130°C for 10 h to allow the Pt atoms to be completely deposited on the surface of MoS2. The mixture was cooled, filtered, and dried at 30°C under vacuum conditions for 10 h.
[0067] (6) The product obtained in (5) was annealed at 260°C for 1 h to finally obtain a composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles (Pt / E-MoS2).
[0068] Example 3
[0069] The preparation method of the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles in this embodiment comprises the following steps:
[0070] (1) 650 mg of ammonium molybdate ((NH4)6Mo7O 24), 550 mg of thiourea (NH2CSNH2) and 320 mg of surfactant PVP were dissolved in 20 mL of deionized water to obtain a uniform mixed solution under stirring.
[0071] (2) The mixed solution prepared in step (1) was heated in a reaction kettle at 260° C. for 20 h.
[0072] (3) The precipitate produced in step (2) is centrifuged, washed, and dried at 70° C. for 15 h to obtain a black solid (MoS2).
[0073] (4) Disperse 180 mg of the black solid obtained in step (3) in 150 mL of a water-ethanol (water to ethanol volume ratio of 13:1) mixed solvent.
[0074] (5) 13 mL of Na2[PtCl6]·6H2O with a concentration of 0.7 mmol / L was injected into the mixed solution obtained in step (4) at a rate of 10 min / mL, and the mixture was incubated at 100°C for 7 h to allow the Pt atoms to be completely deposited on the surface of MoS2. The mixture was cooled, filtered, and dried at 70°C under vacuum conditions for 15 h.
[0075] (6) The product obtained in (5) was annealed at 350°C for 5 h to finally obtain a composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles (Pt / E-MoS2).
[0076] Example 4
[0077] The preparation method of the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles in this embodiment comprises the following steps:
[0078] (1) 600 mg of ammonium molybdate ((NH4)6Mo7O 24 ), 500 mg of thiourea (NH2CSNH2) and 280 mg of surfactant PVP were dissolved in 15 mL of deionized water to obtain a uniform mixed solution under stirring.
[0079] (2) The mixed solution prepared in step (1) was heated in a reaction vessel at 180° C. for 20 h.
[0080] (3) The precipitate produced in step (2) is centrifuged, washed, and dried at 30° C. for 15 h to obtain a black solid (MoS2).
[0081] (4) Disperse 180 mg of the black solid obtained in step (3) in 225 mL of a water-ethanol (water to ethanol volume ratio of 13:1) mixed solvent.
[0082] (5) 13 mL of 1.4 mmol / L Na2[PtCl6]·6H2O was injected into the mixed solution obtained in step (4) at a rate of 40 min / mL, and the mixture was incubated at 110°C for 8 h to allow the Pt atoms to be completely deposited on the surface of MoS2. The mixture was cooled, filtered, and dried at 30°C under vacuum conditions for 15 h.
[0083] (6) The product obtained in (5) was annealed at 260°C for 5 h to finally obtain a composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles (Pt / E-MoS2).
[0084] Example 5
[0085] The preparation method of the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles in this embodiment comprises the following steps:
[0086] (1) 650 mg of ammonium molybdate ((NH4)6Mo7O 24 ), 550 mg of thiourea (NH2CSNH2) and 300 mg of surfactant PVP were dissolved in 15 mL of deionized water to obtain a uniform mixed solution under stirring.
[0087] (2) The mixed solution prepared in step (1) was placed in a reaction vessel and heated at 220° C. for 17 h.
[0088] (3) The precipitate produced in step (2) is centrifuged, washed, and dried at 50° C. for 13 h to obtain a black solid (MoS2).
[0089] (4) Disperse 160 mg of the black solid obtained in step (3) in 160 mL of a water-ethanol (water to ethanol volume ratio of 10:1) mixed solvent.
[0090] (5) 7 mL of 1.0 mmol / L Na2[PtCl6]·6H2O was injected into the mixed solution obtained in step (4) at a rate of 25 min / mL, and the mixture was incubated at 100°C for 9 h to allow the Pt atoms to be completely deposited on the surface of MoS2. The mixture was cooled, filtered, and dried at 70°C under vacuum conditions for 10 h.
[0091] (6) The product obtained in (5) was annealed at 350°C for 3h to finally obtain a composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles (Pt / E-MoS2).
[0092] Comparative Example 1
[0093] The preparation method of molybdenum disulfide in this comparative example is different from that in Example 1 in that the surface is not modified with platinum nanoparticles, and comprises the following steps:
[0094] (1) 625 mg of ammonium molybdate ((NH4)6Mo7O24 ), 525 mg of thiourea (NH2CSNH2) and 300 mg of surfactant PVP were dissolved in 17 mL of deionized water to obtain a uniform mixed solution under stirring.
[0095] (2) The mixed solution prepared in step (1) was heated in a reaction kettle at 220° C. for 17 h, and then cooled to room temperature and collected.
[0096] (3) The precipitate produced in step (2) was centrifuged, thoroughly washed with water and ethanol, and dried at 50° C. for 13 h to obtain a black solid (E-MoS2).
[0097] Application Examples
[0098] The Pt / E-MoS2 obtained in Example 1, the molybdenum disulfide obtained in Comparative Example 1, and the Pt / C catalyst purchased on the market were used for the preparation of electrocatalytic green hydrogen. In the process of electrocatalytic hydrogen production, the specific steps for preparing the working electrode are as follows: 5 mg of catalyst and 10 mg of conductive carbon black (EC-300J) are mixed with 500 μL of deionized water, 470 μL of isopropanol, and 30 μL of 117 were mixed to form a catalyst ink, which was then ultrasonicated in cold water for 3 h. Subsequently, 60 μL of the above catalyst ink was evenly coated on a carbon cloth (size 1 cm × 1 cm), and the mass loading of the catalyst on the electrode was 0.3 mg cm -2 .
[0099] The above working electrode was tested for hydrogen production performance by water electrolysis using linear sweep voltammetry (LSV). The specific test method is as follows:
[0100] In an alkaline electrolyte environment, the performance of the electrode for hydrogen production by water electrolysis was studied by linear sweep voltammetry. -1 The scanning rate is set at 0.5V to 0.2V, and the current-potential curve is obtained within a certain potential range of -0.5V-0.2V. The overpotential of the electrode at different current densities can be obtained according to the curve, so as to compare the performance of different catalysts through the overpotential at a specific current density.
[0101] The linear sweep voltammetric curve of the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles prepared by the present invention is as follows: Figure 6 As can be seen from the figure, the sample prepared in Example 1 has a -2 The overpotential at the current density is 35mV, and at 100mAcm -2 The overpotential at this current density is 221 mV, while the overpotential of Pt / C catalyst is 221 mV at 10 mA cm -2 and 100mA cm -2The current densities of E-MoS2 catalyst are 41mV and 236mV respectively at 10mA cm -2 and 100mA cm -2 The current density is 213mV and 441mV respectively, which are significantly higher than the overpotential of the obtained sample. The test results show that Pt / E-MoS2 has excellent HER catalytic activity. The overpotential specific data of the catalysts prepared in different embodiments and comparative examples, and Pt / C are shown in Table 1.
[0102] Table 1. Current density at 10 mA cm -2 and 100mA cm -2 The overpotential
[0103]
[0104] As can be seen from Table 1, the overpotential of Pt / E-MoS2 prepared in Example 1 is significantly lower than that of Comparative Example 1 and Pt / C catalyst, and has good catalytic performance.
[0105] The working electrode was subjected to a chronoamperometry test for the stability of the hydrogen production cycle by electrolysis of water. The specific test method is as follows:
[0106] In an alkaline environment, taking the Pt / E-MoS2 catalyst with a mass fraction of 1.2% as an example, in 1M KOH solution, at 1Acm -2 The anion exchange membrane water electrolyzer (AEMWE) based on 1.2% Pt / E-MoS2 and IrO2 was tested at 1A cm -2 The voltage changes with time under continuous testing for 1000 hours. If the voltage fluctuation is small, it means that the electrode has good cycle stability in alkaline environment. At the same time, the electrode is also stable under low density (such as 20mA cm -2 ) to observe the current stability. For example, 1.2% Pt / E-MoS2 can maintain a stable current density for 110 hours, indicating that it has good alkaline cycle stability. The stability curve of the obtained composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles is shown in Figure 7 The results show that Pt / E-MoS2 has a current density of 20 mA cm -2 Able to run stably for 110 hours.
[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles, characterized in that: Here are the steps: (1) Dissolve ammonium molybdate, thiourea and polyvinyl pyrrolidone in deionized water to obtain a mixed solution I; and obtain MoS2 by heat treatment; (2) dispersing the MoS2 obtained in step (1) in a mixed solvent of water and ethanol to obtain a mixed solution II; slowly adding a Na2[PtCl6]·6H2O aqueous solution to the mixed solution II, subjecting the mixed solution to high temperature treatment, cooling, filtering, and drying to obtain a product; (3) The product obtained in step (2) is annealed to obtain a composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles.
2. The method for preparing the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles according to claim 1, characterized in that: In the step (1), the mass ratio of ammonium molybdate, thiourea and polyvinyl pyrrolidone is (60-65):(50-55):(28-32); the concentration of ammonium molybdate in the mixed solution I is 30-44 g / L.
3. The method for preparing the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles according to claim 2, characterized in that: The heat treatment temperature in step (1) is 180-260° C. and the time is 15-20 hours.
4. The method for preparing the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles according to claim 3, characterized in that: The volume ratio of water to ethanol in the mixed solvent in step (2) is (7-13):1; the concentration of MoS2 in the mixed solution II is 0.8-1.2 g / L.
5. The method for preparing the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles according to claim 4, characterized in that: The concentration of the Na2[PtCl6]·6H2O aqueous solution in step (2) is 0.7-1.4 mmol / L; the rate of slowly injecting the Na2[PtCl6]·6H2O aqueous solution is 10-40 min / mL; the volume ratio of the Na2[PtCl6]·6H2O aqueous solution to the mixed solution II is 1:(10-23).
6. The method for preparing the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles according to claim 5, characterized in that: The temperature of the high temperature treatment in step (2) is 90-130° C. and the time is 5-10 hours.
7. The method for preparing the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles according to claim 6, characterized in that: The annealing treatment in step (3) is performed at a temperature of 260-350° C. and for a time of 1-5 h.
8. A composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The molybdenum disulfide has a vertically aligned structure and edge-rich sulfur sites.
9. Use of the composite electrocatalyst of molybdenum disulfide loaded with platinum nanoparticles according to claim 8 in hydrogen evolution reaction under alkaline conditions.
10. The use according to claim 9, characterized in that: In the hydrogen evolution reaction, the composite electrocatalyst of molybdenum disulfide supported on platinum nanoparticles has a high conductivity at 10 mA cm -2 At a current density of 20 mA cm, the overpotential is 35 mV; and at 20 mA cm -2 The device can run stably for more than 110 h at a current density of 2.5 %.
Citation Information
Patent Citations
Preparing method of electrocatalysis hydrogen generation molybdenum disulfide@PVP material
CN109967131A
Catalyst as well as preparation method and application thereof
CN116730410A
Preparation method of molybdenum disulfide loaded platinum nanocluster composite electrocatalyst for hydrogen production by alkaline electrolysis of water
CN117822023A
Cited By
Fluorine and chlorine co-doped carbon nanosheet loaded platinum nanocluster hydrogen evolution catalyst and preparation method thereof
CN122358233A